1999
DOI: 10.1088/0952-4746/19/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation exposure and mortality: second analysis of the National Registry for Radiation Workers

Abstract: The National Registry for Radiation Workers (NRRW) is the largest epidemiological study of UK radiation workers. Following the first analysis published in 1992, a second analysis has been conducted using an enlarged cohort of 124,743 workers, updated dosimetry and personal data for some workers, and a longer follow-up. Overall levels of mortality were found to be less than those expected from national rates; the standardised mortality ratio for all causes was 82, increasing to 89 after adjusting for social cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
2
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(125 citation statements)
references
References 28 publications
10
104
2
9
Order By: Relevance
“…Table I give some examples of cohort studies with their precision and the number of excess deaths, expected on the basis of the ERR/Sv provided by the SHN study. This confirms the expected lack of precision of national study of the nuclear power industry and shows that the 15-country study is less precise than the three-country study and even less precise than the English study based on the National registry of radiation workers (Muirhead et al, 1999). Despite a larger number of cancer deaths, the 15-country study has less expected excess deaths than the three-country study and, even if the number of excess deaths is about the same as in the English study, the latter is more precise because the dose range is larger and as a consequence the slope is estimated with a greater precision.…”
Section: What Is a Large Cohort Study?supporting
confidence: 69%
“…Table I give some examples of cohort studies with their precision and the number of excess deaths, expected on the basis of the ERR/Sv provided by the SHN study. This confirms the expected lack of precision of national study of the nuclear power industry and shows that the 15-country study is less precise than the three-country study and even less precise than the English study based on the National registry of radiation workers (Muirhead et al, 1999). Despite a larger number of cancer deaths, the 15-country study has less expected excess deaths than the three-country study and, even if the number of excess deaths is about the same as in the English study, the latter is more precise because the dose range is larger and as a consequence the slope is estimated with a greater precision.…”
Section: What Is a Large Cohort Study?supporting
confidence: 69%
“…No significant associations were reported in Sellafield, Atomic Weapons Establishment, Hanford, Japanese, or combined US, UK and Canadian cohorts. [305][306][307][308][309][310][311][312] Furthermore, there were no trends in NHL risk based on cumulative radiation dose in these cohorts. Other studies have reported no significant associations among US military personnel who participated in atmospheric nuclear weapons tests, 313 participants in the UK atmospheric nuclear weapons tests, 314 residents living near nuclear installations, 315,316 uranium miners, 317 dental workers 318 or cohort members of the National Dose Registry of Canada.…”
Section: Radiation Exposurementioning
confidence: 81%
“…An RDR also might help illuminate other controversies, like that over doses and confidence limits in Canadian worker research showing an excess relative cancer risk per 100 mSv that is 13 times higher than the radiation risk revealed by the atomic bomb study 21 and 33 times higher than the radiation risk revealed by the British worker study. 22 By controlling for factors like confounders, healthy-worker effects, and dose misclassifications; providing direct, individualized, exposure data; offering larger samples and longer exposure periods; and building on worker studies, 20 the RDR could facilitate exploratory data analysis, clarify low-dose controversies, make radiation studies cheaper and easier, and provide a model for other nations to follow. should not have to ensure that radiation employees are informed about and consent to occupational, cumulative, and relative radiation doses and risks, because employers have no control over nonoccupational risks.…”
Section: Additional Arguments For a Radiation-dose Registrymentioning
confidence: 99%